2021
DOI: 10.1155/2021/1525619
|View full text |Cite
|
Sign up to set email alerts
|

Hypoxia Upregulates NOTCH3 Signaling Pathway to Promote Endothelial-Mesenchymal Transition in Pulmonary Artery Endothelial Cells

Abstract: Background. To investigate the effect of hypoxia on pulmonary artery endothelial cells and the role of NOTCH3 in endothelial-mesenchymal transition (EnMT) and to provide a research model for pulmonary disease and explain the pathogenesis of the pulmonary disease. Methods. Pulmonary artery endothelial cells were divided into two groups and cultured in normoxic and hypoxic environments, respectively. QPCR, western blot, and immunofluorescence were used to detect endothelial cell-specific marker protein and mRNA … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 32 publications
1
4
0
Order By: Relevance
“…This may involve upregulation of α-SMA (α-smooth muscle actin), a Notch3 signaling procontractile target. 30,31 Hypoxia is a potent inducer of oxidative stress 32 as observed in our study. Hypoxic alterations to vascular reactivity improved with fasudil and 4-PBA, suggesting a role for ROCK and ER stress in PH vascular dysfunction.…”
Section: Discussionsupporting
confidence: 75%
See 1 more Smart Citation
“…This may involve upregulation of α-SMA (α-smooth muscle actin), a Notch3 signaling procontractile target. 30,31 Hypoxia is a potent inducer of oxidative stress 32 as observed in our study. Hypoxic alterations to vascular reactivity improved with fasudil and 4-PBA, suggesting a role for ROCK and ER stress in PH vascular dysfunction.…”
Section: Discussionsupporting
confidence: 75%
“…This may involve upregulation of α-SMA (α-smooth muscle actin), a Notch3 signaling procontractile target. 30 , 31 …”
Section: Discussionmentioning
confidence: 99%
“…Previous studies have revealed that Hes5 and Hes1 regulated the remodeling of blood vessels and the arterial specification of endothelial cells in brain vascular development 28 . Hypoxia caused a high expression of Notch3 and Hes1 and upregulated the Notch3 pathway to promote endothelial–mesenchymal transition in pulmonary artery endothelial cells (PAECs) 29 . The inhibition of Hes1 might play a protective role in endothelial cells under cholesterol stimulation via the PI3K/AKT signaling pathway 30 .…”
Section: Discussionmentioning
confidence: 99%
“… 28 Hypoxia caused a high expression of Notch3 and Hes1 and upregulated the Notch3 pathway to promote endothelial–mesenchymal transition in pulmonary artery endothelial cells (PAECs). 29 The inhibition of Hes1 might play a protective role in endothelial cells under cholesterol stimulation via the PI3K/AKT signaling pathway. 30 The Notch1 expression and transcriptional activity increased under hypoxic conditions in human PAECs (hPAECs).…”
Section: Discussionmentioning
confidence: 99%
“…In this permissive genetic background, abnormalities of the innate and adaptive immune systems, coupled with increased expression of ET-1 [26] and reduced production of nitric oxide synthase [27], cause vasoconstriction, intimal proliferation and hypoxia with consequent endothelial-mesenchymal transition and conversion to fibroblast-like cells [28]. In parallel, ET-1 activates and re-programs the functional phenotypes of vascular smooth muscle cells, microvascular pericytes and tissue fibroblasts into pro-fibrogenic cell In a predisposed genetic background, an exogenous trigger that targets blood vessels may determine the engagement of inflammatory molecules and cells of the innate immune system.…”
Section: Figurementioning
confidence: 99%